2015
DOI: 10.1002/pat.3508
|View full text |Cite
|
Sign up to set email alerts
|

Maleated glycidyl 3-pentadecenyl phenyl ether with styrene: synthesis and application as compatibilizer in SBR/silica composite

Abstract: Maleated glycidyl 3‐pentadecenyl phenyl ether with styrene (MGS) was synthesized from glycidyl 3‐pentadecenyl phenyl ether (GPPE), maleic anhydride (MAH) and styrene (St) in the presence of AIBN initiator at 80°C, and then the resultant MGS was applied as a compatibilizer to prepare SBR/silica composites. Meanwhile, the commercial compatibilizer bis‐(triethoxysilylpropyl) tetrasulfide (named Si69) added into composite was also prepared for comparison purpose. The synthetic MGS structure was characterized by GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…When rubber nanocomposite is applied to tire treads, the anti-wet skid performance is generally correlated with the tanδ values at 0 • C [46,47]. The higher the tanδ value at 0 • C is, the better the anti-skid performance is.…”
Section: Dynamic Mechanical Properties Of Silica/ssbr/br Compositesmentioning
confidence: 99%
“…When rubber nanocomposite is applied to tire treads, the anti-wet skid performance is generally correlated with the tanδ values at 0 • C [46,47]. The higher the tanδ value at 0 • C is, the better the anti-skid performance is.…”
Section: Dynamic Mechanical Properties Of Silica/ssbr/br Compositesmentioning
confidence: 99%
“…Due to the excellent performance, more than half of silica had been applied to rubber industry. Particularly, precipitated silica had become the main reinforcing materials besides carbon black, which had been used as reinforcing filler partially or exclusively for NR, epoxidized natural rubber (ENR), styrene‐butadiene rubber (SBR), silicone rubber, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the cocrosslinking reaction might occur between the MNSF-2 fiber and SBR during vulcanization process, resulting in improved interface bonding and comparative mechanical properties of the modified fibers/SBR tread compounds. Furthermore, the superior elongation at break of MNSF-2/SBR compounds confirmed the formation of flexible interfacial bond between fibers and rubber matrix [26]. The developed flexible interface bond of tread compound is feasible to the well balance properties for a truck tire service.…”
Section: Resultsmentioning
confidence: 62%
“…Our previous research results had confirmed that short nylon fibers waste maintained their length upon mixing and had reinforcing effects on Ethylene Propylene Diene Monomer rubber [25]. Moreover, in our lab we had successfully employed Glycidyl 3-Pentadecenyl Phenyl Ether (GPPE), a renewable derivative from cashew nut industry, as a compatibilizer to improve the interface adhesion between SBR and nanoparticle fillers [26,27]. The presence of the epoxy propyl ether group and C 15 unsaturated side chain in GPPE molecule, as shown in Figure 1, facilitates chemical reactions of GPPE with many chemical compounds [28].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation